2022
DOI: 10.3389/fphar.2022.888968
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study on the Reproductive Toxicity of Tripterygium Glycosides in Rats

Abstract: Tripterygium glycoside tablet (TGT) is a common clinically used and effective non-steroidal immunosuppressant. However, its reproductive toxicity limits its application in pediatric immune diseases, warranting the study of the molecular mechanism behind its reproductive toxicity. In the present study, 4-week-old male Sprague Dawley (SD) rats were provided TGT through continuous gavage with a clinically equivalent dose of 12 mg/kg for 12 weeks. The reproductive toxicity of TGT was recorded, and its toxicity mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, because TG could reduce the concentration and survival rate of sperms and make the convoluted meridians vacuolated (Dai et al. 2022 ), its reproductive toxicity limits the application in some patients at childbearing age, and couples with childbearing demand need to take it cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because TG could reduce the concentration and survival rate of sperms and make the convoluted meridians vacuolated (Dai et al. 2022 ), its reproductive toxicity limits the application in some patients at childbearing age, and couples with childbearing demand need to take it cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that a number of metabolic genes and pathways are regulated by PPARα, including fatty acid oxidation (FAO) in mitochondria, fatty acid activation and binding, fatty acid elongation, synthesis and decomposition of lipid droplets and triglycerides and lipoprotein metabolism [ 30 ]. Omics data from previous studies have shown that GA can reduce the accumulation of lipids, affect the metabolism of long-chain fatty acids, and regulate the activities of the cytochrome P450 and PPARα signaling pathways to reduce hepatotoxicity caused by TG [ 10 , 31 ]. In this study, the TG groups showed lower levels of PPARα mRNA transcription and protein expression, whereas the presence of GA increased PPARα levels.…”
Section: Discussionmentioning
confidence: 99%